Molecular Diffusion through Cyanobacterial Septal Junctions - Nieves-Morión, Mercedes (mBio, 2017)
Heterocyst-forming cyanobacteria grow as filaments in which intercellular molecular exchange takes place. During the differentiation of N(2)-fixing heterocysts, regulators are transferred between cells. In the diazotrophic filament, vegetative cells that fix CO(2) through oxygenic photosynthesis provide the heterocysts with reduced carbon and heterocysts provide the vegetative cells with fixed nitrogen. Intercellular molecular transfer has been traced with fluorescent markers, including calcein, 5-carboxyfluorescein, and the sucrose analogue esculin, which are observed to move down their concentration gradient. In this work, we used fluorescence recovery after photobleaching (FRAP) assays in the model heterocyst-forming cyanobacterium Anabaena sp. strain PCC 7120 to measure the temperature dependence of intercellular transfer of fluorescent markers. We find that the transfer rate constants are directly proportional to the absolute temperature. This indicates that the “septal junctions” (formerly known as “microplasmodesmata”) linking the cells in the filament allow molecular exchange by simple diffusion, without any activated intermediate state. This constitutes a novel mechanism for molecular transfer across the bacterial cytoplasmic membrane, in addition to previously characterized mechanisms for active transport and facilitated diffusion. Cyanobacterial septal junctions are functionally analogous to the gap junctions of metazoans.